Penambahan Optical Distribution Point (ODP) Menggunakan Metode Branching Dalam Rancangan Jaringan Fiber To The Home (FTTH) Di Gedung G Lantai 3 Politeknik Negeri Padang - Rifaa Dhiyannisa Yuseliani (Jurnal Ilmiah Poli Rekayasa, 2022)
Fiber To The Home (FTTH) is a network that uses fiber optics. One of the devices on FTTH is optical distribution point (ODP). There are two methods of ODP installation, namely by connecting aerial cables directly to ODP and branching. Branching is a method of branching FTTH devices. In previous studies branching was carried out in the closure. However, in the study there was a drawback, namely the branching in the closure must be carried out by connecting fiber optic cables which requires high accuracy. Therefore, this study discusses branching in ODP with the 1: 2 passive splitter method and dropcore cable. Therefore, with this method branching can be done without connecting fiber optic cables. The result of this study is branching with a 1:2 passive splitter, one of the outputs to the ODP Closure Area of the passive splitter 1:8 has a high attenuation value when at the customer's home, which is 32.23dB, compared to other outputs in the passive splitter 1:2 directly connected to the OTB has a attenuation value of 23.53dB. In contrast to branching, using a dropcore cable to the ODP passive splitter 1:4 as a branching tool produces a attenuation value of 26.55dB, which is in accordance with the standards for all four outputs. The high attenuation value affects the quality of the network in the customer's home. Therefore, good branching is to use a dropcore cable. The allowable attenuation value in the customer's home is less than 28dB in accordance with itu-T G.984 standard.